The Influence of Zakat Fund and Macroeconomic Variable on Economic Development in Indonesia and Bangladesh - Ridlo, Musalim; Mochlasin (Journal of Indonesian Economic Research, 2024)
This study aims to analyze the effect of zakat funds and macroeconomic variables on economic development in Indonesia and Bangladesh for the 2010-2019 period. This study uses secondary data with a time series data model of zakat funds, macroeconomic variables consisting of taxes, unemployment, economic growth (GDP), poverty, and the human development index (HDI) from both countries. Furthermore, the data were tested using multiple linear regression models and simultaneous model tests, to obtain test results and complex analysis of the effects of exogenous and endogenous variables on the economic development of the two countries, with the help of the EVIEWS application version 9. The results showed that zakat funds had an effect on positive and significant effect on economic growth in both countries, taxes have a negative and insignificant effect on economic growth in both countries, poverty has a positive and insignificant effect in Indonesia, and insignificant negative in Bangladesh. While the results of the influence of the simultaneous model include; there is a simultaneous effect of zakat, unemployment, and poverty on economic growth in Indonesia and Bangladesh. There is no simultaneous effect between the variables of tax, unemployment, and poverty on economic growth, and there is a simultaneous effect between the variables of the human development index (HDI), poverty, and unemployment on economic growth in Indonesia and Bangladesh.